2008
DOI: 10.2500/aap.2008.29.3132
|View full text |Cite
|
Sign up to set email alerts
|

Addressing steroid phobia: Improving the risk–benefit ratio with new agents

Abstract: Inhaled corticosteroids (ICSs) are the preferred first-line preventative therapy for asthma of all severity levels. Although these drugs have been proven efficacious, concerns of adverse systemic affects due to both long- and short-term use continue to limit patient compliance with dosing regimens. Deficits in bone growth, bone density, and hypothalamic-pituitary-adrenal axis function, in addition to cataract formation and elevated intraocular pressure/glaucoma, have been associated with ICS use in some studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…ICS exert their antiinflammatory effects on asthmatic airways and result in the improvement of symptoms and lung function as well as a decrease in bronchial responsiveness and the risk for asthma exacerbations in different age groups [2,11,16,22,35]. However, the possible risk of systemic undesirable effects due to regular use of corticosteroids is a common concern for both physicians and parents of patients in the pediatric age group [29]. Among the side effects of ICS, hypothalamic-pituitary-adrenal (HPA) axis suppression (HPA-AS) and decrease in growth velocity have frequently been investigated [7,34].…”
Section: Introductionmentioning
confidence: 99%
“…ICS exert their antiinflammatory effects on asthmatic airways and result in the improvement of symptoms and lung function as well as a decrease in bronchial responsiveness and the risk for asthma exacerbations in different age groups [2,11,16,22,35]. However, the possible risk of systemic undesirable effects due to regular use of corticosteroids is a common concern for both physicians and parents of patients in the pediatric age group [29]. Among the side effects of ICS, hypothalamic-pituitary-adrenal (HPA) axis suppression (HPA-AS) and decrease in growth velocity have frequently been investigated [7,34].…”
Section: Introductionmentioning
confidence: 99%
“…A newer drug, ciclesonide, does not become activated until it deposits in lung tissue. 43 However, even if there is no oral bioavailability, systemic exposure can still occur when inhaled corticosteroids are absorbed directly into the lung after deposition. It appears that alveolar deposition may give rise to more systemic exposure than airway deposition because particles depositing in the alveoli are not removed by mucociliary clearance and because the alveoli may be more permeable to diffusion than the airway.…”
Section: Expiration and Problems With Aerosol Depositionmentioning
confidence: 99%
“…Systemic exposure to inhaled corticosteroids can lead to short-term growth suppression in children, decreases in bone mineral density, and possibly an increase in cataracts. [41][42][43] Whereas the potential role of corticosteroids have high levels of oropharyngeal deposition (up to 80% with pressurized MDIs and dry powder inhalers), and it is crucial that, when this oropharyngealdeposited drug is subsequently swallowed, its systemic exposure be kept as low as possible. The oral bioavailability of beclomethasone as one the oldest of the inhaled corticosteroids is approximately 20%, fluticasone is approximately 1%, and mometasone less than 1%.…”
Section: Expiration and Problems With Aerosol Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although glucocorticosteroids and long-acting β-2 antagonists (LABA) are available as inhalers for treatment of asthma, inhaled glucocorticosteroids are preferred as the first-line drug because of their potent anti-inflammatory effects. However, it has been reported that long-term use of inhaled highdose glucocorticosteroids causes systemic side effects such as adrenal suppression, decreased bone mass, cataracts and glaucoma [2][3][4]. Alternatively, leukotriene receptor antagonists are widely used as oral medications in the management of chronic asthma for their antiinflammatory effects [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%